The Al-Rich Part of the Fe-Al Phase Diagram - Li, Xiaolin; Scherf, Anke; Heilmaier, Martin; Stein, Frank (Journal of phase equilibria and diffusion, 2016)
The Al-rich part of the Fe-Al phase diagram between 50 and 80 at.% Al including the complex intermetallic phases Fe 5 Al 8 (ε), FeAl 2 , Fe 2 Al 5 , and Fe 4 Al 13 was re-investigated in detail. A series of 19 alloys was produced and heat-treated at temperatures in the range from 600 to 1100 °C for up to 5000 h. The obtained data were further complemented by results from a number of diffusion couples, which helped to determine the homogeneity ranges of the phases FeAl 2 , Fe 2 Al 5 , and Fe 4 Al 13 . All microstructures were inspected by scanning electron microscopy (SEM), and chemical compositions of the equilibrium phases as well as of the alloys were obtained by electron probe microanalysis (EPMA). Crystal structures and the variation of the lattice parameters were studied by x-ray diffraction (XRD) and differential thermal analysis (DTA) was applied to measure all types of transition temperatures. From these results, a revised version of the Al-rich part of the phase diagram was constructed.